ChemInform Abstract: Enantioselective N‐Heterocyclic Carbene‐Catalyzed Annulations of 2‐Bromoenals with 1, 3‐Dicarbonyl Compounds and Enamines via Chiral α, β‐Unsaturated Acylazoliums. Issue 37 (22nd August 2013) - Yetra, Santhivardhana Reddy; Bhunia, Anup; Patra, Atanu; Mane, Manoj V.; Vanka, Kumar; Biju, Akkattu T.
Abstract The title reaction results in the formation of synthetically and medicinally important dihydropyranones and dihydropyridinones in high enantioselectivities.